2020
DOI: 10.1177/0143034320934524
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk and mental health in Chinese adolescents: The moderating role of psychological capital

Abstract: The current study examined the associations among cumulative risk, psychological capital and adolescents’ anxiety/depression and life satisfaction. Chinese adolescents ( N = 1473, grades 7 to 12, ages 12 to 18, 52.1% female) completed self-report cumulative risk, psychological capital, anxiety/depressive symptoms and life satisfaction questionnaires. Cumulative risk was associated with anxiety/depression and life satisfaction. Psychological capital demonstrated a compensatory effect on youth adjustment. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…They found a moderating and mediating effect of resilience, and concluded that resilience may decrease the negative effect of neuroticism, and enhance the positive effect of extraversion, agreeableness and conscientiousness on depressive symptoms. Others investigated resiliency over multiple systems, such as family, school, peers [ 14 ▪▪ , 15 , 16 ]. Poorer quality in interpersonal relationships (with a parent, teacher, or peers) was related to mental health problems in children.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a moderating and mediating effect of resilience, and concluded that resilience may decrease the negative effect of neuroticism, and enhance the positive effect of extraversion, agreeableness and conscientiousness on depressive symptoms. Others investigated resiliency over multiple systems, such as family, school, peers [ 14 ▪▪ , 15 , 16 ]. Poorer quality in interpersonal relationships (with a parent, teacher, or peers) was related to mental health problems in children.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…Chung et al [ 15 ] also found that living with a single parent was associated with lower resilience, which in turn was associated with higher levels of depression. Additionally, a study in 1473 high school students found that a construct of psychological capital (including hope, efficacy, resilience and optimism) buffered the influence of cumulative risk (an index of youth adjustment, family, school, peer and neighborhood aspects) on anxiety and depression symptoms but not life satisfaction [ 16 ]. Interestingly, a study in 456 high school students found that psychological capital was also positively related to flourishing.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…When dealing with external pressure or risk, individuals can mobilize their own resources to deal with them ( Molden et al., 2016 ), thus effectively reducing the risk of adverse emotions ( Kwok, 2019 , Schotanus-Dijkstra et al., 2017 ). Compared with individuals with low psychological capital, individuals with high psychological capital have lower risk of psychological exhaustion because they have more psychological resources ( Xiong et al., 2020 ). Especially in the unsafe environment of the COVID-19 epidemic situation, high psychological capital can buffer the adverse effects of external stress and risk on individual psychology, and reduce individual anxiety experience.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high psychological capital is positively correlated with positive emotions ( Avey et al., 2008 ). Related research shows that psychological capital can positively predict adolescents’ life satisfaction and negatively predict anxiety, and has a moderating effect on the relationship between cumulative family risk and anxiety ( Xiong et al., 2020 ). Using psychological capital to cope with stress and risks can be seen as a self-regulating process that mobilizes its own psychological resources to meet external challenges ( Molden et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation